CCD observations of binary clusters in the Magellanic Clouds. - Bhatia, R. K.; Cannon, R. D.; Hatzidimitriou, D. (European Southern Observatory Conference and Workshop Proceedings, 1987)
The existence of binary clusters in the Large Magellanic Cloud has been discussed recently. A survey of the LMC on UKSTU plates yielded a total of 69 pairs of clusters with a center-to-centre separation of less than ≡18 pc (for a distance modulus of 18.4 for the LMC). Statistical arguments suggest that taking chance line-ups into account, a significant fraction of the pairs found must be physically associated at the 7σ level. A series of observations have been undertaken in order to establish the physical association of the pairs.
Keywords: Magellanic Clouds:Star Clusters; Star Clusters:Interactions; Star Clusters:Magellanic Clouds